Effects of extra metals added in an autoclave during acidic ammonothermal growth of m-plane GaN single crystals using an NH4F mineralizer. (17th August 2018) - Tomida, Daisuke; Bao, Quanxi; Saito, Makoto; Kurimoto, Kohei; Sato, Fukuma; Ishiguro, Tohru; Chichibu, Shigefusa F.
Abstract: The presence of an extra Al metal in an autoclave tremendously improved the overall quality of m -plane GaN single crystals grown by the acidic ammonothermal method using an NH4 F mineralizer. Although the growth rate was commonly decreased by adding an extra metal such as Al, Si, Ca, or Ti, the crystal coloration was mostly suppressed and the crystal mosaics were decreased, and the near-band-edge excitonic fine structure was observed in the low-temperature photoluminescence spectrum only when Al was present. The results likely indicate that the extra Al suppressed the incorporation of oxygen into m -planes of GaN owing to the oxygen gettering effect.